Kierunki doskonalenia polskiego prawa wykroczeń: [Trends of improvement of Polish regulation of petty-offences] (Studia Prawnicze / The Legal Studies, 1981)
This article evaluates the Polish regulation of petty-offences and proposes the main direction of changes this regulation should undergo in the near future. The notion petty-offences, in the Polish legal system, covers the whole of material, procedural and structural regulations concerning the responsibility for the smallest penal acts, under the sanction not exceeding '3 months of imprisonment, 3 months of limitation of liberty or fine up to 5000 zi. The said regulation is contained in the codification of the law of petty-offences of 1971. This codification is composed of: the code of petty-offences, the petty-offences proceeding's code and the law regulating the organisation of administrative organs judging in the cases of petty-offences.After a throughout examination of the whole of the mentioned codification together with regulations issued after 1971 and their practical application in the years of 1972-1980, author comes to the conclusion that the most serious weakness of the Polish law of petty-offences in an extensive separation of judgements given in this cases from the sphere of courts' activities, and at the same time, excessive corelation of this judgements with the state's administration. This has a negative influence upon the independence of ruling bodies and on correctness of their judgements. The separation of adjudgements in the cases of petty-offences from the activities of courts is one of the causes for existing inconsistencies of state's penal policy.Among many proposed changes, author considers as the most important, an introduction of an appeal to the general courts as the only mean of appeal from the decisions of the special organs judging in the cases of petty-offences. This proposal is connected with the proposition to abolish the second instancy of administrative organs judging in the cases of petty-offences and with demand for the placement of the supervision over those administrative organs with the Ministry of Justice ‘(to replace the supervision carried out by the Ministry of Interior and local organs of administration). Ruling exclusively as organs of the first instancy the administrative organs judging in the cases of petty-offences would have no right to give judgements whose consequences could be detention